Systemic lupus erythematosus complicated by noncirrhotic portal hypertension: A case report and review of literature - Yang, Qi-Bin (World J Clin Cases, 2018)
A 48 year-old Chinese woman suffering from polyarthritis, irregular fever and trichomadesis was admitted to the hospital. A diagnosis of systemic lupus erythematosus (SLE) was made based on polyarthritis, pancytopenia, reduced complement 3, multiple positive autoantibodies, a positive Coomb’s test and protein in her urine. In addition, splenomegaly was detected during physical examination and confirmed by abdominal ultrasonography and magnetic resonance imaging, indicating that the patient had SLE and portal hypertension. Further negative investigations ruled out the possibility of cirrhosis. The patient was diagnosed with active SLE complicated by noncirrhotic portal hypertension (NCPH) without liver histopathology, due to the patient’s refusal for liver biopsy. Portal vein diameter and splenomegaly decreased following treatment with methylprednisolone, hydroxychloroquine and metoprolol tartrate. To date, SLE complicated by NCPH has rarely been reported, as it is under-recognized clinically as well as pathologically. Here we describe a case of SLE complicated by NCPH and review the literature for its characteristics, which may contribute to improving the recognition of NCPH and reducing missed and delayed diagnosis of this disorder.